A case report of concurrent embryonal rhabdomyosarcoma and diffuse large B-cell lymphoma in an adult without identifiable cancer predisposition. Issue 1 (December 2017) - Mathias, M.; Ortiz, M.; Magnan, H.; Ambati, S.; Slotkin, E.; Chou, A.; Walsh, M.; Offit, K.; Moskowitz, C.; Kentsis, A.; Wexler, L.
Abstract Background Diffuse large B-cell lymphoma (DLBCL) is the most common form of non-Hodgkin lymphoma. Rhabdomyosarcoma, the most common soft tissue sarcoma of childhood. makes up less than 1% of solid malignancies in adults with around 400 new cases each year in the United States. They have not previously been reported concurrently. Case presentation A 37 year old woman presented with painful enlarging leg mass. Biopsy of the mass was consistent with embryonal rhabdomyosarcoma. Staging imaging revealed a PET avid anterior mediastinal lymph node. Excisional biopsy of this mass was consistent with diffuse large B-cell lymphoma. Hybridization capture-based next-generation DNA sequencing did not reveal shared somatic tumor mutations. Germline analysis did not show identifiable aberrations ofTP53 or other heritable cancer susceptibility genes. She was treated with a personalized chemotherapy regimen combining features of R-CHOP and Children's Oncology Group ARST 0331. Conclusions This case illustrates a unique clinical entity successfully treated with a personalized chemotherapeutic regimen.